Role of Maternal Adverse Childhood Experiences on Infant Neglect: A Multi-Perspective Approach - Zhang, Xuan (Journal of interpersonal violence, 2025)
We explored the intergenerational transmission effects of maternal adverse childhood experiences (ACEs) and infant neglect from multiple perspectives. The study included a sample of postpartum mothers and infants (N = 550) from the outpatient child health care department of a tertiary hospital in Jinan, Shandong Province, China. Our investigation followed three main lines of inquiry. First, the association of overall maternal ACEs with infant neglect was estimated. Secondly, the cumulative and independent effects of maternal ACEs on infant neglect were explored using the Adverse Childhood Experience Questionnaire-Revised (ACEQ-R) with 14 types of ACEs. Finally, the different patterns of 14 maternal ACEs were identified, and the association between the different patterns and infant neglect was explored. There were three main findings. First, infants born to mothers with ACEs experienced higher levels of neglect compared to those born to mothers without ACEs. Second, infants born to mothers with three or more subtypes of ACEs experienced the greatest levels of neglect, with maternal childhood physical neglect emerging as a particularly influential factor. Third, infants in the “median maternal ACEs” and “high maternal neglect and poor peer relationship” groups experienced more severe neglect than those in the “low maternal ACEs” group. These results suggest that early life experiences substantially shape future parenting behaviors, such as infant neglect.